Suma incisal superior e inferior de los estudiantes del Colegio Adolfo Valarezo de la ciudad de Loja en el periodo marzo - julio del 2015 - Paucar Narváez, Tatiana Maribel (2015)
The tooth size is expressed as the mesiodistal dimension of each piece, which is determined from childhood, this can be influenced by various factors such as race, ethnicity, herencia. El model analysis is one of the most used, the accuracy and easy application. This measure does not change after eruption unless it is affected by other factors such as interproximal caries, here dimension is a stable factor in tooth size / arch size relationship. The proposed Mayoral incisor index determines if the patient has microdontia or macrodontia , for this index takes into account the mesial- distal diameter of the four upper incisors , considering as normal the result of the sum of the maxillary incisors that were among the 28 to 32mm. In the present work was to identify the incisal amount of students 13 years old of Adolfo Valarezo school in the period from March to July 2015; compare if there is a difference in the incisal summation that present the students by sex; establish if the measures proposed by the mayoral index are equal or if there is a difference in the results obtained in our population. The model analysis is one of the most used, the accuracy and easy application. It allows an approach to the final diagnostic and further analysis. The study group were students 13 years old of Adolfo Valarezo school of Loja city. The sample size was one hundred lower and upper models. A form of data collection was used to compare the proposed Mayoral (value of 32 mm) with the sum of the four upper incisors of the population: in general, divided by gender. In the population of this research have a number of students some anomalies in size as are in men two students presented 33 mm, 2 presented 34 mm and 4 had 36 mm, regarding female 1 student present 33 mm and 1 was measured 34 mm which were diagnosed in the upper incisal macrodontia sum; 3 students female and 3 male students were diagnosed macrodontia in less than 26 mm incisal record sum; One female student was diagnosed microdontia in less than 19 mm incisal record sum. Through this research showed that patients have similar characteristics to the population studied by this index Mayoral serving us as an alternative to the basic orthodontic diagnosis and general dentist to diagnose changes in size and can give to a plan treatment accorde and time. Keywords: macrodontia, microdontia, incisal sum.